UNSUR PRIMORDIALISME DALAM KISAH NABI MUSA AS DAN DUA LAKI-LAKI YANG BERKELAHI (TELAAH QS. AL-QASAS AYAT 15 ANALISIS INTERPRETASI JORGE J.E. GRACIA) - Tri Ulva Chandra; Aldo Marezka Putra (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
The purpose of writing this article is to review the primordialism that occurs in the story of Musa As' meeting with two people who were fighting and made Musa As accidentally kill someone. This story is summarized in the QS. al-Qasas/28:15. The methodology used in this research is a qualitative method in the nature of a literature review using Jorge J.E. Gracia's hermeneutic interpretation analysis which examines broad aspects of the verse, both from the historical, meaning and implications, thus producing an interpretive function, namely the historical function. , meaning function, and implicative function. The results of this research are first, this verse was revealed as an effort to strengthen the Muslims who were oppressed by the polytheists like Pharaoh who oppressed Moses and his people and also in line with the general condition of Mecca society at that time which still upheld the values of fanaticism. ethnicity and class. Second, through the function of the meaning of the story of Moses in this verse, it is alleged that there is an attitude of primordialism which encouraged Moses to help a man from his people who was fighting, where the man was someone who often caused chaos. Third, the implication function of this story is relevant to multicultural Indonesian society. Apart from having a positive attitude in strengthening solidarity, primordialism is also often the cause of conflict between groups, especially in Indonesia